Bidirectional Role of β2-Adrenergic Receptor in Autoimmune Diseases - Wu, Li; Tai, Yu; Hu, Shanshan; Zhang, Mei; Wang, Rui; Zhou, Weijie; Tao, Juan; Han, Yongsheng; Wang, Qingtong; Wei, Wei (Frontiers in Pharmacology, 2018)
Disorder of the sympathetic nervous system (SNS) is closely related to the pathogenesis of various autoimmune diseases (ADs). Catecholamine triggered beta2-adrenergic receptor (β2-AR) signaling is important in creating a bidirectional response in the progression of ADs due to factors including diverse expression patterns, single nucleotide polymorphisms (SNPs), biased signals, and desensitization of β2-AR, as well as different subtypes of Gα binding to β2-AR. In this review, we summarize the actions of β2-AR signaling in regulating the functions of immunocytes and in the pathogenesis of ADs, while the application of β2-AR agonists or antagonists in treating major types of ADs is also discussed. We suggest that restoring the immune balance via a soft regulation of the expression or activation of β2-AR is one of the promising therapeutic strategies for systematic ADs.